THE INFLUENCE OF IMAGINATIVE DESCRIPTION GAME TOWARDS STUDENTSâ€™ VOCABULARY MASTERY AT THE SECOND SEMESTER OF THE EIGHTH CLASS AT SMP NEGERI 1 GUNUNG SUGIH LAMPUNG TENGAH IN 2013/2014 - Wahyuningsih, Sri (Lentera: Jurnal Ilmiah Kependidikan, 2016)
English is an International language, and in Indonesia English as the first foreign language that should be taught from elementary school up to university. Many students get difficulties in learning English especially in meaning vocabulary. In this research the writer tries to investigate â€œimaginative description gameâ€ as a technique in teaching vocabulary.The objective of this research is to know the influence of imaginative description game towards studentsâ€™ vocabulary mastery at the eighth class. The research was conducted at the second semester of eighth class of SMP Negeri 1 Gunung Sugih Lampung Tengah in 2013/2014. The student of 8C consists of 26 students as experimental class was taugh by imaginative description game and 8B consist of 26 students as a control class was taugh by conventional technique.Before conducting the research, the writer asumed thet the students had the same characteristics, qualities and also status. The result of the research showed that there was positive influence of using imaginative description game towards studentsâ€™ vocabulary mastery at the second senester of the eighth class at SMP Negeri 1 Gunung Sugih Lampung Tengah in 2013/2014. It is shown by the result of data analysis in which t-test = 5.22 and t-table = 2.00 at significance level 5% and 2.66 at significance level 1%. So ???????? is accepted because t â‰¥ ????????????????(1âˆ’????) and ????0 is rejected. It means that avergae score of studentsâ€™ vocabulary mastery that is taught by using vacation game (???? 1= 73.35) is higher than who are taught by using conventional technique (???? 2= 52.5) at second semester of eighth class at SMP Negeri 1 Gunung Sugih Lampung Tengah in 2013/2014.